PART - Mental health - Work - Relations - PART - Questionnaires 1-3 - Forsell, Yvonne; Lundberg, Ingvar; Lavebratt, Catharina (Karolinska Institutet, 2012)
To increase knowledge in the field of mental illness the PART study (Mental health, work and relationships) was started, an epidemiological study on psychological morbidity among 20-64-year olds in the Stockholm County population.
Mental health is a public health problem, and if it increases, it is alarming in both human and socio-economic aspects. It is therefore important to identify the causes and if possible affect them. It is also important to identify risk groups in order to provide help as soon as the first symptoms appear, so that a long-term suffering can be prevented.
In the PART study 10 441 individuals (5798 women and 4643 men) between 1998 and 2000, answered questions on living conditions, including working conditions and mental illness. This represented a response rate of 53%. Of these, 1100 participated in a psychiatric interview. PART II, which ran 2001-2003 was a continuation of this study, where those who responded to the first survey, answered an additional questionnaire with essentially the same issues. There were 8613 individuals who responded to both questionnaires.
Substudies within PART are among others Work and mental health and Drinking habits and alcohol problems (AUDIT test).

Purpose:

The aims of the PART study:
- To describe risk and protective factors for mental ill-health in the adult (20-64 years old) population of the Stockholm County.
- To analyse the association between social, somatic, cognitive and mental ill-health.
- To validate screening instruments for assessment of mental ill-health.
- To analyse factors associated with meetable need of psychiatric, psychological and social services.
- To analyse consequences of mental ill-health.
- To analyse the outcome of both treated and untreated mental ill-health.
- To describe the frequency of the most common axis I psychiatric symptoms and syndroms in the adult population.

För att öka kunskaperna inom området psykisk ohälsa startades PART (Psykisk hälsa, Arbete, RelaTioner), en epidemiologisk studie som under sin första fas har kartlagt den psykiska sjukligheten bland 20-64-åringar i Stockholms läns befolkning.
Psykisk ohälsa är ett folkhälsoproblem och om den ökar är det alarmerande både ur mänskliga och samhällsekonomiska aspekter. Det är därför viktigt att identifiera orsaker och om möjligt angripa dem. Det är också angeläget att identifiera riskgrupper för att kunna ge hjälp redan när de första symtomen dyker upp, så att ett långvarigt lidande kan förhindras.
I PART-studien besvarade 10 441 personer (5798 kvinnor och 4643 män) mellan 1998 och 2000 en enkät om levnadsförhållanden, bland annat arbetsförhållanden och psykisk ohälsa. Detta utgjorde en svarsfrekvens på 53%. Av dessa deltog 1100 i en psykiatrisk intervju. I PART II som pågick 2001-2003 genomfördes en fortsättning av denna studie där de som svarade på den första enkäten fick ytterligare en enkät med i huvudsak samma frågor. Det var 8613 personer som svarade på båda enkäterna.
Delstudier inom PART är bl.a. Arbetsliv och psykisk ohälsa och Alkoholvanor och alkoholproblem (AUDIT-testet).

Syfte:

Att beskriva risk- och skyddsfaktorer för psykisk ohälsa i befolkningen, att analysera samband mellan sociala faktorer, kroppslig ohälsa, kognitiva funktioner och psykisk ohälsa, att validera screeningsinstrument för psykisk ohälsa i befolkningen, att analysera faktorer som har samband med behov av psykiatriska, psykologiska och sociala behandlingsinsatser, att analysera sociala konsekvenser av psykisk ohälsa, att analysera förloppet av behandlad och obehandlad psykisk ohälsa, att analysera effekt av arbetslivs- och arbetsmarknadsförhållanden på psykisk ohälsa och att beskriva förekomsten av de vanligaste psykiatriska symtomen/diagnoserna (depression, ångest och alkohol-missbruk/beroende) i den vuxna befolkningen
PART - Psykisk hälsa - Arbete - Relationer - PART - Enkätundersökningarna 1-3
Keywords: hospitalization; sjukhusvistelser; sick leave; sjukfrånvaro; demography; demografi; Diagnosis; Diagnos; Blood Specimen Collection; Blodprovstagning; Mental Disorders; Psykiska störningar; Pathological Conditions, Signs and Symptoms; Patologiska tillstånd, tecken och symtom; Socioeconomic Factors; Socioekonomiska faktorer; Anxiety; Ångest; Risk Factors; Riskfaktorer; Alcoholism; Alkoholism; Alcohol Drinking; Alkoholkonsumtion; Alcohol-Related Disorders; Alkoholmissbruk; Adaptation, Psychological; Psykologisk anpassning; Work; Arbete; Workload; Arbetsbelastning; Epidemiology; Epidemiologi; Phobic Disorders; Fobier; Public Health; Folkhälsa; Health Status; Hälsotillstånd; Life Change Events; Livsavgörande händelser; Drug Utilization; Läkemedelsförsörjning; Depression; Depression; Panic Disorder; Paniksyndrom; Interpersonal Relations; Mellanmänskliga relationer; Psychiatric Status Rating Scales; Psykiatriska skattningsskalor; Mental Health; Psykisk hälsa; Psychotropic Drugs; Psykofarmaka; Disease Progression; Sjukdomsförlopp; Suicidal Ideation; Självmordstankar; Social Problems; Sociala problem; Obsessive-Compulsive Disorder; Tvångssyndrom; Occupations; Yrken; Feeding and Eating Disorders; Mat- och ätstörningar; HEALTH; HÄLSA; Medical and Health Sciences; Medicin och hälsovetenskap; Psychiatry; Psykiatri; Occupational Health and Environmental Health; Arbetsmedicin och miljömedicin